Employee performance in the Housing, Settlement, and Land Services Department of Central Kalimantan Province: the impact of job stress and job satisfaction - Song, Jelina Rivani; Christa, Usup Riassy; Panjaitan, Olivia Winda Ony (JSM: Jurnal Sains Manajemen, 2024)
This study seeks to empirically elucidate the impact of work stress and job satisfaction on employee performance in Housing, Settlement, and Land Services Department of Central Kalimantan Province. The research methodology employed in this study is a quantitative associative research strategy. The participants in this study were public servants working in the housing, residential, and land services sectors in the province of Central Kalimantan. The total number of participants was 39, and they were selected using a saturated sample technique. The research instrument employed in this study utilized the Likert scale methodology. The findings indicated that workplace stress has a detrimental impact on performance, whereas job happiness has a beneficial and substantial impact on performance. Additionally, work stress and job contentment have a concurrent influence on performance